Post-Pandemic Healthcare Stocks: The Impact of Microeconomic Factors and Investor Behavior - Reza Fauzan Risch; Hermanto Siregar; Zenal Asikin (Universitas Mercu Buana, 2026)
Objective: This study investigates the influence of microeconomic factors and investor behavior on stock prices in the healthcare sector following the COVID-19 pandemic, aiming to identify which factors most significantly affect stock performance.Methodology: A quantitative approach was used with panel data regression analysis through the Random Effect Model (REM), selected based on the Hausman test (p = 0.7357). Independent variables included revenue, operating costs, return on equity (ROE), earnings per share (EPS), price-to-earnings ratio (PER), debt-to-equity ratio (DER), current ratio (CR), and investor behavior.Finding: The analysis shows that revenue, operating costs, EPS, PER, DER, and CR significantly affect stock prices, while ROE and investor behavior have no significant effect. The model has a high explanatory power with an R² of 0.928, indicating it accounts for 92.8% of the variation in healthcare stock prices.Conclusion: Internal financial factors are more dominant than investor behavior in influencing stock prices. Improving financial efficiency and performance transparency is recommended to strengthen investor confidence, and future research should include macroeconomic variables to broaden the analysis.